Modeling strategic planning for sustainable competitive advantage in supply chain management - Al-Shammari, Minwir (Business: Theory and Practice, 2023)
This paper proposes a knowledge-based customer-centric strategic model to respond to environmental challenges and achieve sustainable competitive advantage (SCA) in the supply chain management (SCM) context. The proposed model strives to leverage knowledge-based distinctive core competencies (DCCs) to improve customer satisfaction and achieve SCA. An exploratory research design has been adopted. The study undertook a systematic literature review approach with 36 articles or books published between 1970 and 2020 to construct the strategic planning model. The paper presents an integrated multi-dimensional model for SCM, including value chain activities, competitiveness strategies, business process re-engineering (BPR), and SCA. The practical result of the article is to develop a theoretical strategic planning model for SCM as a holistic framework for using the company’s DCCs and creating an SCA in a highly competitive and dynamic business environment. The proposed model comprehensively covers the supply chain (SC)’s competitive advantage strategy. For businesses that tend to adapt and triumph, the proposed model helps reduce order cycle times, reduce inventory levels, increase accuracy and efficiency, reduce costs, and improve customer service and satisfaction.